HAKIKAT PERKEMBANGAN MANUSIA - Anisa Purnama Sari; Siti Fatimah Mustari, Della Bella Julia Balqis, Linda Yarni (CV. ADIBA AISHA AMIRA, 2024)
This research aims to find out what is meant by development, what is meant by growth and maturity, what are the characteristics of development and what are the principles of development. This type of research uses a qualitative approach, the research tries to solve problems and discuss them in detail at the present time regarding development and growth and maturity. The main method of this research is library research, namely research that utilizes library sources to obtain data, which uses data sources from reference books which contain specific information, and is usually used as a reference in development, growth and regarding maturity, articles from journals or periodicals, as well as other sources of information that are relevant to the discussion, so that they can complement the data to arrive at conclusions. The results of this research show that development is not just about height and weight a person's body or a person's abilities, but rather a process integration of many complex structures and functions. As well as from the material on the nature of development, there is an understanding of development and growth, the characteristics of development, and developmental principles.